Maximum heat recovery and utilization system in a municipal activated sludge Fluidized Bed Incineration (FBI) plant: A case study for Bursa, Turkey - (:unkn) unknown (Water Environment Federation, 2016)
An innovative application of a heat recovery system (HRS) was introduced for the fluidized bed incineration (FBI) system designed for 400 tons per day dewatered municipal activated sludge in an advanced biological nutrient removal sewage treatment plant in Bursa, Turkey. The planned HRS will provide maximum heat utilization by recovering unused available heat in the flue gas through two different sets of heat exchanging systems. This planning aims to achieve autogenous operational conditions of the incinerators and generate 2.5 MW electricity. The present case study will provide an insight to similar real case applications about integration of a HRS into a conventional FBI plant. The design approach presented has significant impact on the overall operational efficiency and economy of the FBI applications for municipal activated sludge incineration. Copyright ©2016 Water Environment Federation.
Keywords: Activated sludge; Electricity generation; Fluidized bed incinerator; Heat recovery